2015
DOI: 10.3329/bjp.v10i3.23714
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal and antispasmodic activities of <i>Polygonum bistorta</i> rhizomes are mediated predominantly through K+ channels activation

Abstract: <p class="Abstract"><em>Polygonum bistorta</em> is a popular medicinal herb used to treat diarrhea. This study provides pharmacological basis to its folk use in diarrhea using <em>in vivo</em> and <em>in vitro</em> assays. Administration of<em> P. bistorta</em>  rhizomes extract to mice offered protection against castor oil-induced diarrhea at 300-1,000 mg/kg and was found safe up to the dose of 5 g/kg. In isolated rabbit jejunum, the extract caused a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The plant extract showed similar potency for its inhibitory effect against CCh and low K + -induced contractions, thus showing PDE-inhibitory and K + -channel opening-like activities, 41 whereas partial inhibition was seen against high K + -induced contractions, implying weak involvement of Ca 2+ -channel inhibition, as concentrations of K + >30 mM, regarded as high K + , are known to cause smooth-muscle contractions through opening of voltage-dependent Ca 2+ channels. 36,41 On the other hand, verapamil, a standard CCB, 41 inhibited spasms mediated by K + at distinctly lower concentrations, as expected from typical CCBs. 28 The inhibitory actions of the plant extract on the PDE enzyme was confirmed by the observation that pretreatment of jejunal tissue with the extract shifted the inhibitory CRCs of isoprenaline to the left, similarly to papaverine, a known inhibitor of PDE 41 that produces spasmolytic effects through increased cAMP as a result of PDE inhibition, 43,44 while verapamil did not affect the isoprenaline curves, as was expected from a standard Ca 2+ antagonist.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The plant extract showed similar potency for its inhibitory effect against CCh and low K + -induced contractions, thus showing PDE-inhibitory and K + -channel opening-like activities, 41 whereas partial inhibition was seen against high K + -induced contractions, implying weak involvement of Ca 2+ -channel inhibition, as concentrations of K + >30 mM, regarded as high K + , are known to cause smooth-muscle contractions through opening of voltage-dependent Ca 2+ channels. 36,41 On the other hand, verapamil, a standard CCB, 41 inhibited spasms mediated by K + at distinctly lower concentrations, as expected from typical CCBs. 28 The inhibitory actions of the plant extract on the PDE enzyme was confirmed by the observation that pretreatment of jejunal tissue with the extract shifted the inhibitory CRCs of isoprenaline to the left, similarly to papaverine, a known inhibitor of PDE 41 that produces spasmolytic effects through increased cAMP as a result of PDE inhibition, 43,44 while verapamil did not affect the isoprenaline curves, as was expected from a standard Ca 2+ antagonist.…”
Section: Discussionmentioning
confidence: 85%
“…As such, any test material that exhibits inhibitory effects against castor oil-induced diarrhea is considered to possess marked antidiarrheal activity. [34][35][36] M. subcordata appears to possess marked antidiarrheal effects, which could be due to the possible presence of gut-relaxant constituent(s). In line with our findings, Akuodor et al 12 reported antidiarrheal effects of the methanol-leaf extract of a similar species, M. crassifolia, with a proposed mechanism of action linked partly to direct inhibitory effects on the propulsive movement of GI-tract smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…A test substance causing complete inhibition of spontaneously contracting rabbit jejunum may indicate its ability to interfere with cytosolic Ca ++ influx. To investigate the possible mechanism of the observed inhibitory effect, the plant material was tested on sustained contraction induced by high [28] and low [42] concentrations of K + . High and low K + mediate contractions through the entry of Ca ++ into muscle cell via voltage dependent Ca ++ channels (VDCCs) and K + channel opening, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This herb can be found all over the world; however it is most common in northern temperate zones like Europe and North America. Polygonum bistorta root (100 g/ml of hydro alcoholic extract) was found to have a powerful inhibitory effect on IL-8 release as an inflammatory moderator in a recent study, which could help to authenticate the conventional use of this plant for GI illnesses caused by H. pylori infection 84 .…”
Section: Polygonum Bistortamentioning
confidence: 99%